Encouraging Safe Wildlife Viewing in National Parks: Effects of a Communication Campaign on Visitors' Behavior. Issue 2 (17th February 2020) - Abrams, Katie M.; Leong, Kirsten; Melena, Sara; Teel, Tara
ABSTRACT: Seeing wildlife in natural habitat is an exciting and powerful experience for national park visitors but is risky for visitors and wildlife alike. National parks have long used educational approaches to inspire visitors to engage in conservation behavior and protect themselves from harm. With record visitation in recent years, national parks must hone their communication strategies that support wildlife conservation and reduce wildlife-caused injuries to visitors. We tested a campaign that strongly promoted the visitor's experience as it aligns with wildlife protection. We measured its effect on how close people approached wildlife in four US national parks. The campaign resulted in fewer visitors observed within unsafe distances to wildlife in three of the four parks. We recommend parks use messages emphasizing the visitor experience gained by engaging in the desired behavior rather than messages that only highlight the importance of wildlife protection.